Social Media Analysis: Utilizing Information Technology for Market Intelligence and Branding of Toraja Coffe Products - Setiawan, Heri Aji (Jurnal Informasi dan Teknologi, 2024)
This research discusses the utilization of social media analytics (AMS) to strengthen brand image and gather market information, specifically in the context of Toraja Coffee products. The aim is to understand consumer needs, improve brand image, and support coffee MSMEs in the Salubarani area, Tana Toraja, South Sulawesi. Through this AMS, it is expected that coffee MSMEs can improve their market knowledge, brand image, and contribution to the local economy. This research was conducted in Salubarani Village, located in Gandangbatu Sillanan District, Tana Toraja Regency, South Sulawesi. This research relies on two types of data, namely primary data and secondary data. The use of purposive sampling technique helped in the selection of informants who met the predetermined criteria. The data collection methods applied in this research include observation, interview, and documentation. The results confirmed that social media analysis is crucial in designing marketing strategies and improving the brand image of Toraja coffee. By understanding consumer preferences through social media platforms, companies can evaluate campaign effectiveness, identify market opportunities, and strengthen brand image. Findings also show that social media plays a crucial role in influencing purchasing decisions and strengthening customer loyalty. In the context of Toraja coffee, social media analytics is a critical success factor in marketing and brandingThe use of Social Media Analytics (AMS) provides great benefits for companies in gaining market intelligence and strengthening brand image. AMS enables customization of marketing strategies, competitor mapping, and identification of hidden opportunities. However, effective use requires a robust IT infrastructure and a well-trained team. Privacy and security challenges must also be addressed. In the context of Kopi Toraja, AMS can help MSMEs strengthen brand image